2020
DOI: 10.1111/opo.12734
|View full text |Cite
|
Sign up to set email alerts
|

The role of the disc damage likelihood scale in glaucoma detection by community optometrists

Abstract: Purpose: Recent guidelines recommend disc damage likelihood scale (DDLS) is recorded for all referrals of suspected glaucoma from community optometrists to hospital eye services (HES) in Scotland. This study aimed to determine whether lower DDLS grades were associated with higher rates of discharge at the first visit to HES. Methods: A retrospective analysis of 618 consecutive new referrals from community optometrists to a university hospital glaucoma service. 65 (10.5%) included DDLS graded by the community o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In Scotland, where the NHS eyecare provided by community optometrists is more comprehensive and better funded, the proportion of referrals discharged at the first visit to glaucoma clinic was 25% for cases of suspected open angle glaucoma or ocular hypertension and 12% in those referred for narrow angles 19 . Another study of CO glaucoma referrals in Scotland found a first visit discharge rate of 25%–27.7%, depending on the information in the referral 18 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Scotland, where the NHS eyecare provided by community optometrists is more comprehensive and better funded, the proportion of referrals discharged at the first visit to glaucoma clinic was 25% for cases of suspected open angle glaucoma or ocular hypertension and 12% in those referred for narrow angles 19 . Another study of CO glaucoma referrals in Scotland found a first visit discharge rate of 25%–27.7%, depending on the information in the referral 18 20 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the accuracy of optometric referrals has mostly studied glaucoma, [17][18][19][20][21][22][23][24][25] which is challenging to diagnose because the signs of early glaucoma are subtle, even to an eye specialist. 26 National Institute for Health and Care Excellence (NICE) glaucoma guidelines in 2009 27 and 2017 28 had a major impact; therefore, this summary of previous literature on optometric referral accuracy concentrates on research published since 2009 in the UK.…”
Section: Referral Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a further study of glaucoma referrals in Scotland found the first visit discharge rate was lower in patients with higher DDLS scores, decreasing from 50% in those with a DDLS of 3, to 0% in those with a DDLS ≥6. 74 No patients with a DDLS of less than 4 were diagnosed with glaucoma at their first visit. This study though was limited by the small number of patients in which DDLS had been recorded.…”
Section: Use Of Ddls In Primary Carementioning
confidence: 99%
“…5 It is commonly accepted and has been incorporated into eye health guidelines for optometrists and ophthalmologists. 7 , 8 The DDLS is limited as a diagnostic tool by the need for expert time to accurately grade images. Automated high-efficacy DDLS grading could offer a powerful screening method.…”
mentioning
confidence: 99%